Optimal Pore Size of Honeycomb Polylactic Acid Films for In Vitro Cartilage Formation by Synovial Mesenchymal Stem Cells. (3rd August 2021) - Yagi, Misaki; Mizuno, Mitsuru; Fujisawa, Ryota; Katano, Hisako; Endo, Kentaro; Ozeki, Nobutake; Sakamaki, Yuriko; Koga, Hideyuki; Sekiya, Ichiro
Abstract : Background . Tissue engineering of cartilage requires the selection of an appropriate artificial scaffold. Polylactic acid (PLA) honeycomb films are expected to be highly biodegradable and cell adhesive due to their high porosity. The purpose of this study was to determine the optimal pore size of honeycomb PLA films for in vitro cartilage formation using synovial mesenchymal stem cells (MSCs). Methods . Suspensions of human synovial MSCs were plated on PLA films with different pore sizes (no pores, or with 5  μ m or 20  μ m pores) and then observed by scanning electron microscopy. The numbers of cells remaining in the film and passing through the film were quantified. One day after plating, the medium was switched to chondrogenic induction medium, and the films were time-lapse imaged and observed histologically. Results . The 5  μ m pore film showed MSCs with pseudopodia that extended between several pores, while the 20  μ m pore film showed MSC bodies submerged into the pores. The number of adhered MSCs was significantly lower for the film without pores, while the number of MSCs that passed through the film was significantly higher for the 20  μ m pore film. MSCs that were induced to form cartilage peeled off as a sheet from the poreless film after one day. MSCs formed thicker cartilage at two weeks when growing on the 5  μ m pore films than on the 20  μ m pore films. Conclusions . Honeycomb PLA films with 5  μ m pores were suitable for in vitro cartilage formation by synovial MSCs.